Kinetic aspects of enzyme-mediated repair of DNA single-strand breaks. (December 2016) - Zhdanov, Vladimir P.
Abstract : Graphical abstract: Abstract : Highlights: The focus is on the repair of DNA single-strand breaks in human cells. The process starts via break detection and processing of damaged ends. The subsequent steps include gap filling and end ligation. The kinetic four-enzyme model proposed describes these steps. The effect of strand unzipping on the end ligation is scrutinized. Abstract: In cells and bacteria, DNA can be damaged in different ways. The efficient damage repair, mediated by various enzymes, is crucial for their survival. Most frequently, the damage is reduced to single-strand breaks. In human cells, according to the experiments, the repair of such breaks can mechanistically be divided into four steps including (i) the break detection, (ii) processing of damaged ends, (iii) gap filling, and (iv) ligation of unbound ends of the broken strand. The first and second steps run in parallel while the third and fourth steps are sequential. The author proposes a kinetic model describing these steps. It allows one to understand the likely dependence of the number of breaks in different states on enzyme concentrations. The dependence of these concentrations on the rate of the formation of breaks can be understood as well. In addition, the likely role of unzipping and zipping of the fragments of broken ends of the strand in the ligation step has been scrutinized taking the specifics of binding of DNA stands into account.